Forma ewidencji a ryzyko podatkowe przedsiębiorstwa - Poszwa, Michał (Accounting And Tax Risk Management, 2008)
There are different rules of taxing incomes of personal partnerships and capital companies in Polish law. Different status in taxes of personal partnerships and capital companies is very controversial. There is a problem appearing, whether the different charging of both kinds of companies disturbs in the wide range the rules of competition. Moreover the different taxing of personal partnerships and capital companies causes the necessity of deciding which form is more profitable for the taxpayer. Setting the cost-effectiveness is very difficult and demands using profit calculation. The final decision about form of business activity is very risky.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 105-114